2008
DOI: 10.1051/agro:2008028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of catch crops on N dynamics and following crops in organic farming

Abstract: Green manure catch crops promote the sustainability of agricultural systems by reducing soil erodibility and by nutrient uptake and transfer to the following main crops. This effect efficiently reduces the risk of nitrate leaching. Biological nitrogen fixation by legume catch crops is an additional benefit, mainly in organic farming. Such crops may, however, reduce nitrogen uptake from the soil and increase nitrate leaching. Additionally, under drought conditions, their extra water consumption may outweigh the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 20 publications
5
46
0
Order By: Relevance
“…In that year, with the exception of Panicum miliaceum L., a statistically significant difference in the yields of spring barley after catch crops and control variant was recorded. Reduction of spring barley yield was extraordinary; after Sinapis alba L. was as much as 44% down when compared to the control Rinnofner et al (2008). Only in extreme years, a very low rainfall in the winter and during the growth and development of spring barley may reduce its yield after grown catch crops, confirming the assertion of Bodner (2013).…”
Section: Resultssupporting
confidence: 68%
“…In that year, with the exception of Panicum miliaceum L., a statistically significant difference in the yields of spring barley after catch crops and control variant was recorded. Reduction of spring barley yield was extraordinary; after Sinapis alba L. was as much as 44% down when compared to the control Rinnofner et al (2008). Only in extreme years, a very low rainfall in the winter and during the growth and development of spring barley may reduce its yield after grown catch crops, confirming the assertion of Bodner (2013).…”
Section: Resultssupporting
confidence: 68%
“…When cover crops are planted to reduce nutrient leaching (N in particular) following a main crop, they are often termed "catch crops." [75,76]. Moreover, growing green manures on site is a way to prevent the often inhibitive handling and transportation costs of other organic inputs [69].…”
Section: Nitrogen Fertilization Using Green Manure and Cover Cropsmentioning
confidence: 99%
“…Conditions that encourage good N production include getting a good stand, optimum soil nutrient levels and soil pH, good nodulation, and adequate soil moisture. The portion of green-manure N available to a following crop is usually about 40% to 60% of the total amount contained in the legume [76]. Interestingly, it has been demonstrated that leguminous cover crops were also able to replace 60% of the chemical N fertilization for cotton production, although the quantity of available N derived from the cover crop was not synchronized with the requirements of the cotton plant [89].…”
Section: Nitrogen Fertilization Using Green Manure and Cover Cropsmentioning
confidence: 99%
“…Common vetch is desirable as green manure mainly for the ability to form vigorous root system that develops nodules at early stages and fixes atmospheric N into the soil (Rinnofner et al, 2008;Vlachostergios et al, 2011). Although a lot of research has been carried out on vetch production (Tuna and Oraka, 2007) there is little information about the contribution of Vicia sativa as green manure.…”
Section: Introductionmentioning
confidence: 99%